PERGARUH_PENGOPERASIAN_FILTER_AKTIF_BERBASIS _KONTROL_PID _TERHADAP_KAPASITAS KERJA TRANSFORMATOR DISTRIBUSI DI GEDUNG_ STUDENT_CENTER_UNIVERSITAS_UDAYANA - Satriyo Agung Pribadi; I_M. Suartika; I_G_N. Janardana (Program Studi Teknik Elektro UNUD, 2021)
The transformer is one of the equipmen for distributing electrical_energy from_mediumvoltage 20 kV to low voltage 380/220 V. Disturbance in the transformer_can_cause_Lossesso that it can disrupt the flow of electric power to consumers. Harmonics_are disturbancescaused by the operation of non-linear loads. This study aims to determine the effect of THDion power Losses and working capacity of transformers at Udayana University Student CenterBuilding with harmonics in the R phase of 10.91%, the S phase of 11.38%, and_the T phase of17.91%. The method used is to perform simulations andanalysis_with_the_results_of_harmonic measurements in Existing conditions, using an activefilter, and an active PID-based filter using the Matlab application. Very optimal results wereobtained using a PID-based active_filter with the results of R = 0.31%, S = 0.30%,_T =0.35%,_and the decrease in the working_capacity_of_the_transformer_decreased_to1%,_according _to_the_ideal_value.